Liturgical Text as Mandorla: windows from the Everyday to the Sacred, from the Sacred to the Everyday - Morgan, Stephen (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)

Ogień zapalony niegdyś na górze Moria: Woltyła i Newman o warunkach dla propozycju Chrystusa'=The fire once kindled on Moriah: Wojtyła and Newman on the conditions for the proposal of Christ - Morgan, Stephen (Jan Paweł II: Komunikacja i Kultura, 2020)

Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular - Morgan, Stephen (USJ Press, 2021)

John Henry Newman and the development of doctrine: encountering change, looking for continuity - Morgan, Stephen (The Catholic University of America Press, 2021)
"In focusing on the gestation of "An Essay on the Development of Christian Doctrine" (1845), John Henry Newman's last work as an Anglican and presaging his transition to Catholicism, this book examines how Newman accounted for doctrinal continuity in the face of evidence of change in the history of the church"--

The combat of truth and error: Newman and Chesterton on heresy - Morgan, Stephen (Lead Kindly Light. Essays for Ian Ker, 2022)

‘Em Procissão Solene a Deus Orando, para os Batéis Viemos Caminhando’—The Long Ebb-Tide of Catholic Public Piety in the Former-Portuguese Enclave of Macao - Morgan, Stephen (Religions, 2021)
When the City of the Name of God of Macao marked 400 years of Portuguese administration in 1956, the Catholic community’s participation was marked by a wide range of activities that included liturgical celebrations, public processions and other devotions that involved large numbers of the lay faithful, members of confraternities, in addition to the clergy and religious of the enclave. Twenty-one years later the Diocese of Macao celebrated its own quatercentenary with celebrations of a decidedly more sober character and at the retrocession of Macao to Chinese control in December 1999, other than a few liturgical events and hierarchical presence at civic ceremonies, the Church was all but invisible. As the Diocese of Macao plans for its 450th anniversary, some of the former richness has begun to return. This paper outlines the long ebb tide and now-nascent flow of the tide of Catholic public piety in Macao over this period by reference to the Catholic religious processions of the City and seeks to offer tentative explanations grounded in the theological, ecclesial, political and cultural winds that have blown across the Pearl River Delta since the end of the Second World War.
Keywords: Catholic Church; China; Macao; Portugal; Vatican II; confrarias; processions; public piety

‘Navigation for an ocean of interminable scepticism’ revisited: John Henry Newman and the place of theology in the university - Morgan, Stephen (International Journal for the Study of the Christian Church, 2021)
The place of theology is under threat in the modern university. It is denied a place, except insofar as it is useful in the training of religious professionals or as a phenomenon in its own right, on the grounds that relate to an unscientific scientism that both makes metaphysical assumptions it itself does not recognise as scientific or denies its own epistemological commitments. This article argues that the notion of education in ‘liberal knowledge’ or ‘universal knowledge’, the idea at the heart of John Henry Newman’s The Idea of a University provides a sufficiently robust counter to these assaults on the place of theology proper in the modern university and that refusing such a place to it undermines the claim of universities to use the name at all. It is precisely the uselessness of theology that guarantees its place in the university committed to universal knowledge and universal enquiry.
Keywords: Derrida; Newman; education; liberal education; religious studies; secularisation; theology; university

Going to Church in Medieval England by Nicholas Orme (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2022)

Ceremonies of the Sarum Missal: A Careful Conjecture by R. J. Urquhart (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

The Fire “Once Kindled on Moriah”: Wojtyła and Newman on the Conditions for the Proposal of Christ - Morgan, Stephen (Newman Studies Journal, 2022)

The Anglican Patrimony in Catholic Communion ed. by Tracey Rowland (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2021)

The Roman Mass: From Early Christian Origins to Tridentine Reform by Uwe Michael Lang - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2023)

Pope John Paul II, ‘Memory and Identity: conversations at the dawn of a millennium’ - Morgan, Stephen (Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference, 2023)

‘Culture and identity – nationality and nationalism: indications for a theological reflection’ - Morgan, Stephen (Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference, 2023)

Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference - Morgan, Stephen (USJ University Press, 2023)

To realize an everyday holiness”: Newman, imagination, and the virtue of religion - Morgan, Stephen (A Guide to the Life and Thought of John Henry Newman, 2023)

Pilgrimage Christian and Secular: a Phenomenological Approach - Yuan, Haojun (USJ Theses and Dissertations, 2021)
In the light of the many kinds of journeys that have been considered pilgrimages, this book uses phenomenology as a method to examine the claim that pilgrimage is a journey to the ‘center’ during which pilgrims seek meaning s for themselves. First, by analyzing a phenomenology of Christian pilgrimage, this work attempts to identify what commonalities, as well as differences, exist between Christian pilgrimage and secular pilgrimage in terms of ‘natural attitude’. Next, by using a phenomenological method, such as transcendental reduction, the distinction between these two types of pilgrimage could be clarified that the happiness sought in Christian pilgrimage is both intentionally spiritual and sustainable, while primarily intellectual or sensory in secular pilgrimage. Lastly, this work seeks to establish whether or not ‘being at leisure’ is the primary element for pilgrims whose aim is to attain an understanding of happiness during a pilgrimage
Keywords: Christian pilgrims and pilgrimages; Phenomenology

What Goes Around Comes Around? The (Non-)Existence of (Divine) Retribution in Ancient Chinese Literature and the Hebrew Bible - Leong, Andrew Chin Hei (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)